Analysis of the Effects of the Addition of Sodium Bicarbonate in the Concrete - Chuquiruna Miranda, Leydy Verónica; Vásquez Peña, Jhordan Stuar; Burga Chávez, Manuel Alexander; Castrejón Calderón, Edwin Alfredo; Taica Guevara, Jhon; Carrion Rabanal, Katia Nataly (LACCEI, 2024)
The objective of this work was to determine the effects of sodium bicarbonate as an additive at 10% concerning the amount of cement, in concrete, by analyzing its properties in the fresh and hardened state (temperature, settlement, setting, resistance to compression, capillarity and absorption) and compare them with normal concrete; For this, 3 samples were tested for each percentage, with a total of 6 test tubes, which were tested in the concrete laboratory of the Universidad Privada del Norte, Cajamarca headquarters. Initially, we searched for our raw materials (fine and coarse aggregate) which were subjected to a series of tests, to subsequently be able to design our concrete. Then, we carry out the tests according to the standards that will be mentioned in a later chapter. As a result, the incorporation of bicarbonate at 10% generates reductions of 33.40% in the mechanical properties of compression resistance. Likewise, we can indicate that the concrete with bicarbonate obtains a temperature of 31.2°C, being 7.6°C higher than a normal concrete. In the case of capillarity and absorption, the samples with the 10% bicarbonate dosage obtained a higher value, this being 341.51, and in absorption a value of 23%, these results being more than double those of the samples without bicarbonate. Setting was the most emblematic test of this research since very high results were obtained, in time in minutes, 28 minutes for the sample with 20% addition of bicarbonate, being 89% faster than a type 1 cement, in the in the case of 10% addition, a time of 135 minutes was obtained, being 49% faster than the setting of a normal cement. It was concluded that bicarbonate accelerates setting, increases absorption and capillarity, but damages and abruptly reduces the properties of the concrete.